Prognostic stratification of molecularly and clinically distinct subgroup in children with acute monocytic leukemia. (26th March 2020) - Liu, Li‐Peng; Zhang, Ao‐Li; Ruan, Min; Chang, Li‐Xian; Liu, Fang; Chen, Xia; Qi, Ben‐Quan; Zhang, Li; Zou, Yao; Chen, Yu‐Mei; Chen, Xiao‐Juan; Yang, Wen‐Yu; et al.
Abstract: Background: The prognosis of children with acute monocytic leukemia (AML‐M5) remains unsatisfactory and the risk profile is still controversial. We aim to investigate the prognostic value of clinical and cytogenetic features and propose a new risk stratification in AML‐M5 children. Methods: We included 132 children with AML‐M5. Overall survival (OS) and progression‐free survival (PFS) were documented. Cox regression was performed to evaluate the potential risk factors of prognosis. Results: The 5‐year‐OS was 46.0% (95% confidence intervals, 41.6%‐50.4%) in all patients. There was significantly lower OS in the age ≤ 3 years old ( P  = .009) and hyperleukocytosis ( P  < .001). The FMS‐like tyrosine kinase 3 ( FLT3 )‐internal tandem duplication ( ITD ) and MLL‐rearrangement carriers were associated with fewer survivors in all patients (37.1% and 36.7%) and chemotherapy‐only group (19.0% and 35.0%). Notably, the number of survivor with MLL‐rearrangement did not increase in hematopoietic stem cell transplant (HSCT) group. According to the Cox regression analysis, HSCT was a significantly favorable factor ( P  = .001), while hyperleukocytosis, age ≤ 3 years old, and BM blast ≥ 70% adversely affected the OS in all patients (all P  < .05). Additionally, FLT3‐ITD was a risk factor for OS in the chemotherapy‐only group ( P  = .023), while hyperleukocytosis and age ≤ 3 years independently contributed to poor PFS (both P  < .05). In comparison to the standard‐risk group, significant poorer outcome was found in the high‐risk group (both P  < .005). Conclusions: We propose that AML‐M5 children with any of MLL‐rearrangement, FLT3‐ITD, hyperleukocytosis, BM blast ≥ 70%, or age ≤ 3 years old are classified into the high‐risk group, and HSCT is beneficial especially in patients with FLT3‐ITD mutation, hyperleukocytosis, and age ≤ 3 years old. Importantly, the choice of HSCT should be made more carefully in children with MLL‐rearrangement for its suboptimal performance. Abstract : Outcomes in high‐risk acute monocytic leukemia‐M5 children with only conventional chemotherapy remain unsatisfactory, and hematopoietic stem cell transplant (HSCT) has proven to be beneficial especially in FMS‐like tyrosine kinase 3‐internal tandem duplication carriers, age ≤ 3 years old and hyperleukocytic patients. The choice of HSCT should be made more carefully in a defined subgroup with MLL‐R for its suboptimal performance.